Navigating The Impact of Outsourcing Rule Changes Under the Omnibus Law on Job Creation - Ode, Mahazanni Najwa Al-Asyifa (Universitas Islam Malang, 2024)
The Job Creation Law introduces fundamental changes in employment in Indonesia. This article discusses the impact of changes in outsourcing rules in the Omnibus Law on job creation. Using research methodology involves an in-depth analysis of legislation and secondary data from the legal literature. The results show that changes to outsourcing rules have complex impacts, with the potential for increased investment and efficiency, but also the risk of decreasing workers' rights. The paper concludes the need for responsive regulation to maintain a balance between the interests of companies and workers, ensuring fairness in labor relations. A better understanding of the complexity of changes to outsourcing rules in the Omnibus Law is expected to help improve policies to support sustainable economic growth and worker welfare. Concluded that changes to outsourcing rules can improve a company's investment and operational efficiency, but also create uncertainty and potential impairment of workers' rights and protections. Therefore, responsive legal protection and transparency of information are crucial to maintaining fairness in employment relations. This journal contributes to a better understanding of the complexity of changes to outsourcing rules in the Omnibus Law and raises awareness for better regulatory adjustments to support economic sustainability and worker welfare.